Funerary Monuments in the Interior of the Roman Province of Dalmatia - Lozić, Edisa (E-Monographiae Instituti Archaeologici Sloveniae, 2021)
The present study deals with the question of the organization of the stonemasonry production of funerary monuments in the interior of the former Roman province of Dalmatia. The aim of the research was to identify a model of stonemasonry production that originated in a mountainous and difficult to traverse area, where the possibilities of water transport of stone material are minimal. The author started from the assumption that production centres formed in some geographical areas during Roman rule, using local limestone sources for their operation. The study includes funerary monuments discovered in present-day Bosnia and Herzegovina and in the western part of Serbia and Montenegro. By combining the methods of macroscopic petrographic analysis of the stone material and typological and spatial analysis, the existence of several production centres was proven. The results of the analyses indicate a very likely that they exploited the local limestone resources. Epigraphic data also made it possible to define their chronological aspect.